Factors that contribute to youthfulness in Youth and Adult Education - Ana Paula dos Anjos de Souza Borges; Carla Jovina de Oliveira Alves; Ana Jovina Oliveira Vieira de Carvalho (Universidade Federal do Oeste da Bahia, 2021)
The present work presents the results of the research carried out as a Conclusion Work for an undergraduate degree in Pedagogy, whose theme referred to the process of youthfulness in Youth and Adult Education (EJA). The research methodology was a qualitative approach, with field research. The research subjects were young students from EJA II classes, two teachers and two pedagogical coordinators. The theoretical basis that supports the research is provided by the studies of Carrano (2007), Freire (1987), Andrade (2006) and Arroyo (2017). At work, it was found that the number of students aged 15 to 19 years enrolled in EJA is high. The causes for youthfulness are many, however, the main one is failure in other educational modalities, which is also related to the pedagogical implications, in addition to the problems experienced outside school. Several changes become imperative in the pedagogical organization of EJA, but the research points and highlights the urgency of changes in the curriculum.